Student Perceptions of Academic Engagement and Student-Teacher Relationships in Problem-Based Learning - Amerstorfer, Carmen M.; Freiin von Münster-Kistner, Clara (Frontiers in Psychology, 2021)
Students’ academic engagement depends on a variety of factors that are related to personal learner characteristics, the teacher, the teaching methodology, peers, and other features in the learning environment. Components that influence academic engagement can be cognitive, metacognitive, affective, social, task-related, communicative, and foreign language-related. Rather than existing in isolated spheres, the factors contributing to an individual’s academic engagement intertwine and overlap. The relationships students cultivate with others are prominent in several of these areas. Positive interpersonal relationships enhance individuals’ enthusiasm for learning (Mercer & Dörnyei, 2020), which benefits sustainable learning success and self-confidence. The relationships between students and teachers and the perceptions students have of their teachers seem to be particularly influential on students’ engagement in academic undertakings. Problem-based learning (PBL), a teaching approach particularly suitable for tertiary education, involves students in authentic problem-solving processes and fosters students’ self-regulation and teamwork. Intensive relationship-building is one of the key characteristics of this student-centered approach (Amerstorfer, 2020). The study reported in this article explores the connection between the academic engagement of 34 students and their perceptions of three instructors in a teacher education program for pre-service English teachers in Austria. An online questionnaire was used to investigate the participants’ perceived academic engagement (effort, dedication, learning success) in a university course that implements PBL as its underlying teaching methodology in comparison to conventional teaching approaches. The study further examined how the students perceived the course instructors’ caring, credibility, communication style, and feedback, which led to new information about how PBL shapes student-teacher relationships. Due to Covid-19, the otherwise face-to-face course was taught online.